(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The question of teaching English for Medical Purposes has been significantly researched over the last few years. English is today’s lingua franca of medical international communication, the same as Greek and Latin were in the past; therefore, it is an essential prerequisite for a medical career. Consequently, teaching medical English should be adapted in order to meet the specific academic and professional needs of students. This paper is focused on the development of communicative competence for medical purpose.